All Days 2012
DOI: 10.2118/154202-ms
|View full text |Cite
|
Sign up to set email alerts
|

Oil Recovery by Sequential Waterflooding: the Effects of Aging at Residual Oil and Initial Water Saturation

Abstract: Sequential waterflooding refers to cycles of flooding for which initial water saturation is re-established after a waterflood by flow of crude oil followed by further waterflooding. In previously reported examples of sequential waterflooding, cores were neither cleaned nor re-aged at high crude oil saturation between floods. Numerous core floods with different rock types showed significant decrease in residual oil saturation from one flood to the next (Loahardjo et al. 2010a). Systematic decrease in residual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Since the theory relating the NMR relaxation time of water in porous media to the pore size distribution was first proposed by Loren and Robinson [19], there have been numerous attempts to characterize the pore-level fluid distributions with respect to the sizes of the pores occupied by the fluid [5,[20][21][22].Generally, longer transverse relaxation times reflect larger pore sizes. In this paper, three types of pore sizes are defined according to relaxation times: large pores (T 2 [ 100 ms), medium-sized pores (10 ms \ T 2 \ 100 ms) and small pores (T 2 \ 20 ms).…”
Section: Fig 4 Comparison Of the Oil Saturation Values Obtained By Imentioning
confidence: 99%
See 1 more Smart Citation
“…Since the theory relating the NMR relaxation time of water in porous media to the pore size distribution was first proposed by Loren and Robinson [19], there have been numerous attempts to characterize the pore-level fluid distributions with respect to the sizes of the pores occupied by the fluid [5,[20][21][22].Generally, longer transverse relaxation times reflect larger pore sizes. In this paper, three types of pore sizes are defined according to relaxation times: large pores (T 2 [ 100 ms), medium-sized pores (10 ms \ T 2 \ 100 ms) and small pores (T 2 \ 20 ms).…”
Section: Fig 4 Comparison Of the Oil Saturation Values Obtained By Imentioning
confidence: 99%
“…After waterflooding, a considerable quantity of oil remains trapped in the porous media and is referred to as residual oil [2,3]. Laboratory core flooding experiments have long been used to investigate residual oil behavior in porous media with respect to waterflooding and a wide range of other processes [4][5][6]. However, the distribution of residual oil and water saturation in porous media cannot be determined quantitatively from either of these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In conventional oil-saturated oil reservoirs, the main influence factors on oil-water seepage and distribution of residual oil saturation are permeability and viscosity [1][2][3][4]. For the unsaturated crude oil in the oil-water transition zone, some scholars at home and abroad have verified that the initial oil saturation has certain influence on the oil-water seepage regularity and the residual oil saturation, 2 but no quantitative study has been made on the influence law of the initial oil saturation on the residual oil saturation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have found that after large-scale and long-term waterflooding, reservoir physical properties such as the pore throat structure and rock wettability may change, thus leading to the increase of displacement efficiency and the decrease of residual oil saturation, which can usually improve the development effect on reservoirs. Through a number of waterflooding experiments on different types of cores, Loahardjo et al confirmed that in the process of sequential waterflooding, the residual oil saturation decreased significantly from one flood to the next.…”
Section: Introductionmentioning
confidence: 99%